An Analysis of Appropriate Bilingual Learning Models for Elementary School Students Creators - Bright, Fatimah Nurussyifa Clever; Adristia, Ananta Sely; Pamulatsih, Titis; Amalia, Fika; Ramadian, Naila Rachma; Fatma, Elia; Widagdo, Arif (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the era of globalization, English proficiency has become a critical skill, yet elementary school students in Indonesia still show relatively low mastery of the language. This article explores various bilingual learning models through a Systematic Literature Review of national studies. The analysis focuses on strategies such as the Global English Class, Inside-Outside Circle, and Cooperative and Collaborative Learning approaches. Findings indicate that bilingual instructionwhen structured, aligned with student characteristics, and supported by competent teachers and adequate resourcessignificantly enhances students' English skills and learning motivation. Flexible, interactive, and engaging teaching models prove more effective in creating a positive learning environment. This study recommends the adoption of adaptive bilingual learning models to improve the quality of primary education in Indonesia.